2020
DOI: 10.3390/en13143618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air-Ducted Blade Design on Horizontal Axis Wind Turbine Performance

Abstract: Wind turbines without pitch control are more preferable from economical point of view but aerodynamic stall affects them more and after a critical wind speed local boundary layer separation occurs. Consequently, their power production is relatively low. In this study, air ducts added on the blade and using the airflow from them the kinetic energy of the low-momentum fluid behind the surface was increased and delay of separation of the boundary layer from the surface was examined The Response Surface Optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Its selection requirements for blade profile design were chosen from large CL/CD values based on the angle of attack (α) [22]. The force of the component perpendicular to the direction of flow is called the lift force (FL), while the force of the component in the direction of flow is called the drag force (FD) [28]. Therefore, the selected airfoil was NACA 4412 [29].…”
Section: Methodology Designmentioning
confidence: 99%
“…Its selection requirements for blade profile design were chosen from large CL/CD values based on the angle of attack (α) [22]. The force of the component perpendicular to the direction of flow is called the lift force (FL), while the force of the component in the direction of flow is called the drag force (FD) [28]. Therefore, the selected airfoil was NACA 4412 [29].…”
Section: Methodology Designmentioning
confidence: 99%
“…In addition, studies on improving the performance of diffuser-augmented wind turbines and Energies 2022, 15, 727 2 of 12 CFD analysis have been conducted. The research to derive the optimal shape through CFD analysis of rotor blade contours in wind turbines with ducts was presented [17][18][19][20]. It was confirmed that the performance of the diffuser type duct varies depending on the yaw angle of the inlet [21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…Typically, a wind turbine blade needs a far-field domain of 10-20 times the rotor diameter [45]. However, considering the calculation cost, area immediately adjacent to the wake of the wind turbine [46], 3D helical vortex structure [47], empirical value [48][49][50], and comparison of the calculation zones of different sizes, the rotation and stationary domains are finally modeled into a cylinder shape with diameters of 1.1 and 4D and heights of 0.22 and 7.22D, respectively. e distance from the inlet to the rotation domain is 2D, and the distance from the outlet to the rotation domain is 5D.…”
Section: Calculation Zones and Boundary Conditionsmentioning
confidence: 99%